The Functions of Thought Experiments in Systematic Theology - Agerbo Mørch, Michael; O. Søvik, Atle (AGATHEOS – European Journal for Philosophy of Religion, 2025)
In this article, we argue that thought experiments have an important and specific role to play within science in general and that they can play the same important role in a specific type of systematic theology. If this line of reasoning succeeds, it provides support for the scientific credibility of systematic theology. We give a summary of a more comprehensive argument for different argumentative functions of thought experiments presented in another article and then we show how the same typology can work within systematic theology. By strengthening or weakening a theory’s consistency, cohesiveness, or comprehensiveness, thought experiments provide critical data to assess the relative strength of a theory. The same goes for theories within systematic theology. We show how thought experiments can test and even falsify theological theories and do this in an intersubjective manner. As such, they support the scientific status of theological theories.